What Are We Telling Our Students? A National Survey of Clerkship Directors' Advice for Students Applying to Internal Medicine Residency - Chretien, Katherine C. (J Grad Med Educ, 2015)
BACKGROUND: Little is known about the advice fourth-year medical students receive from their advisors as they prepare to apply for residency training. OBJECTIVE: We collected information on recommendations given to medical students preparing to apply to internal medicine residencies regarding fourth-year schedules and application strategies. METHODS: Clerkship Directors in Internal Medicine conducted its annual member survey in June 2013. We analyzed responses on student advising using descriptive and comparative statistics, and free-text responses using content analysis. RESULTS: Of 124 members, 94 (76%) responded, and 83 (88%) advised fourth-year medical students. Nearly half (45%) advised an average of more than 20 students a year. Advisors encouraged students to take a medicine subinternship (Likert scale mean 4.84 [1, strongly discourage, to 5, strongly encourage], SD = 0.61); a critical care rotation (4.38, SD = 0.79); and a medicine specialty clinical rotation (4.01, SD = 0.80). Advisors reported they thought fourth-year students should spend a mean of 6.5 months doing clinical rotations (range 1–10, SD = 1.91). They recommended highest academic quartile students apply to a median of 10 programs (range 1–30) and lowest quartile students apply to 15 programs (range 3–100). Top recommendations involved maximizing student competitiveness, valuing program fit over reputation, and recognizing key decision points in the application process. CONCLUSIONS: Undergraduate medical advisors recommended specific strategies to enhance students' competitiveness in the Match and to prepare them for residency. The results can inform program directors and encourage dialogue between undergraduate medical education and graduate medical education on how to best utilize the fourth year.